Oxidative Nanopatterning of Titanium Surface Influences mRNA and MicroRNA Expression in Human Alveolar Bone Osteoblastic Cells - Maidy Rehder Wimmers Ferreira; Roger Rodrigo Fernandes; Amanda Freire Assis; Janaína A. Dernowsek; Geraldo A. Passos; Fabio Variola; Karina Fittipaldi Bombonato-Prado (International Journal of Biomaterials)
Titanium implants have been extensively used in orthopedic and dental applications. It is well known that micro- and nanoscale surface features of biomaterials affect cellular events that control implant-host tissue interactions. To improve our understanding of how multiscale surface features affect cell behavior, we used microarrays to evaluate the transcriptional profile of osteoblastic cells from human alveolar bone cultured on engineered titanium surfaces, exhibiting the following topographies: nanotexture (N), nano+submicrotexture (NS), and rough microtexture (MR), obtained by modulating experimental parameters (temperature and solution composition) of a simple yet efficient chemical treatment with a H2SO4/H2O2 solution. Biochemical assays showed that cell culture proliferation augmented after 10 days, and cell viability increased gradually over 14 days. Among the treated surfaces, we observed an increase of alkaline phosphatase activity as a function of the surface texture, with higher activity shown by cells adhering onto nanotextured surfaces. Nevertheless, the rough microtexture group showed higher amounts of calcium than nanotextured group. Microarray data showed differential expression of 716 mRNAs and 32 microRNAs with functions associated with osteogenesis. Results suggest that oxidative nanopatterning of titanium surfaces induces changes in the metabolism of osteoblastic cells and contribute to the explanation of the mechanisms that control cell responses to micro- and nanoengineered surfaces.